Tributação de software exame da constitucionalidade da incidência do ISS e do ICMS-Mercadoria sobre a licença de uso de programa de computador disponibilizado eletronicamente - Padilha, Maria Ângela Lopes Paulino (2016)
The current doctorate thesis has as primary goal to examine the constitutionality of taxation, by the states and municipalities, through the ICMS-M and ISS, respectively, on the use of software licensing (computer program) available electronically by means of the Internet. In the first part of the work, the study begins discoursing about the computing history, the distinction between the basic components of the system (hardware and software) and the creation of the World Wide Web, to then deal with the impacts on society resulting from innovations in the field of Information Technology associated with advances in telecommunications, particularly the Internet, stand out in the end the technological repercussions for the positive law. Continuing the cognitive path, it will be examined the legal nature of the computer program, a copyright protection as intellectual work and the treatment given by Law nº 9.609/98, aiming to build a software definition not only attentive to its technical nature but also conformed to its legal discipline. Subsequently, it proceeds to the examination of the economic exploitation of computer programs, directly related to their forms of contracting ruled by private law, while highlighting the emerging business practice of Software as a Service (SaaS), in comparison with the traditional model licensing Software as a Product. In the final fundamental approach to any tax study focused on legal business with the software, it analyzes concise formats the theme from a perspective compared with the legislation and case law of other countries and with international law, in order to seek solid semantic-pragmatic references to minutiae the proposed scientific object. Engaging the second part of this theoretical force on the Brazilian legal tax system, it analyzes the basic constitutional principles of national legal order, the rigid distinction of taxation powers by the 1988 Constitution, with the dogmatic deepening in the interpretation of the terms used by the constituent to empower the political entities to establish taxes, as well as the role of complementary law as an adjustment mechanism that ensures the functioning of the tax system. Therefore, based on the methodology of the tax incidence matrix-rule, draw up the material criterion of the ICMS-M and ISS, with the aim of define the expressions “operations relating to the circulation of goods” and “provide services of any kind” strictly demarcating the factual core of their chances of incidence. After the constitutional boundaries were defined and addressed to the legislator in the election of the facts to be taxed by ICMS-M and the ISS, initiated the third and final part of this thesis, in order to guide, based on the assumptions set out in previous chapters, thorough legal diagnosis of these tax implications on software use licenses available electronically if it consists of a providing service, circulation of goods operation or diverse legal category